A Shared Vision : Examining the Contributions of FORTHEM Member Universities to Intercultural Competence Development - Pruknerová, Tereza (2024)
This research investigates how the FORTHEM Alliance, one certain network within the European University Initiative, promotes intercultural competence among its member universities. By examining the policies and practices of three universities – the University of Jyväskylä, the Johannes Gutenberg University Mainz, and the University of Agder – this study explores how the alliance contributes to developing intercultural skills among students and staff. A qualitative case study approach was employed, involving semi-structured interviews with four university employees involved in maintaining the FORTHEM Alliance at their respective institutions. Findings reveal a strong alignment between the alliance's goals and member universities' initiatives, such as student mobility, language training, and intercultural collaboration. While the alliance demonstrates significant efforts, expanding its scope beyond European values, strengthening staff involvement, and addressing challenges in virtual mobility are crucial for further enhancing intercultural competence. The research contributes to understanding how university alliances can promote intercultural skills and informs future strategies for promoting internationalisation and cross-cultural collaboration.